MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIMAYANG, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Anwar , Miftakhul; Dzatilah, Ridho (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service activity aims to introduce Sharia Banking to the Community of Cimayang Village, Pamijahan District, Bogor Regency, West Java Province. In this community service, activities are carried out based on the transparency and participation method. The result of this community service is that the people of Cimayang Village know more about Syariah Banking in detail.